WO3nanotubes−SnO2nanoparticles heterointerfaces for ultrasensitive and selective NO2detections - Jirasak Sukunta (2018)
© 2018 In this work, the SnO2nanoparticles−WO3nanotubes heterostructures are reported for the first time and systematically investigated for NO2detection. The hybrid SnO2−WO3sensing films were fabricated by thermal decomposition of WS2nanotubes loaded flame-spray-made SnO2nanoparticles with varying WS2contents (0.5–10 wt%). Characterizations by X-ray diffraction, electron microscopy, thermogravimetric, differential thermal analysis and X-ray photoelectron spectroscopy indicated that hexagonal WS2nanotubes were completely converted to orthorhombic WO3nanotubes and well-dispersed within polycrystalline tetragonal SnO2nanoparticles. The gas-sensing results revealed that the addition of WO3nanotubes to SnO2nanoparticles led to the substantial enhancement of sensor response towards NO2. Specifically, the 5 wt% WO3loaded SnO2sensor exhibited an ultra-high response of ∼12,800 to 5 ppm NO2with good recovery stabilization at a low optimal operating temperature of 150 °C. In addition, the WO3-loaded SnO2sensor presented high NO2selectivity against CH4, NO, C2H5OH, C3H6O, H2S and H2. The enhanced NO2sensing properties may be ascribed to the formation of WO3nanotubes/SnO2nanoparticles n-n hetero interfaces and the enhanced accessible surface areas of highly active sites for chemisorbed NO2species. Therefore, SnO2nanoparticles−WO3nanotubes composite structure prepared by flame spray pyrolysis and thermal decomposition is highly promising for highly sensitive and selective NO2-sensing applications.